Psychotherapy for late-life psychopathology – Updates to promote aging in place - Aisenberg-Shafran, Daniela (Frontiers in Psychology, 2022)
Psychopathology in late life does not always meet the criterion for a psychiatric diagnosis. Nevertheless, it affects the aging person, their family, employers, and society as a whole. Making psychotherapy accessible for older adults, allowing aging in place, must overcome barriers of mobility, stigma, and emotional difficulty to ask for help. Hence, dedicated counseling and treatment centers should be established in the local authorities for the older adults and their caregivers. Such a local center is described, providing low-cost psychotherapy within an academic environment, accompanied by research to promote suitable therapy of older adults, as well as training programs for professional therapists, not just psychologists, with unique emphasis on late-life psychopathology. This model should be implemented, the more the merrier.